DNA Authentication of Indonesian Leaffish Pristolepis grooti from Kelekar River and Ogan River in South Sumatra Based on Cytochrome C Oxidase Subunit I (COI) Gene - Mochamad Syaifudin (Journal of Tropical Biodiversity and Biotechnology, 2023)
Indonesian leaffish Pristolepis grooti, an endemic species, are distributed in the region of Sumatra, Riau, Bangka Belitung and Kalimantan. However, there has been a decline in the population recently. This research purposed to investigate the mitochondrial DNA cytochrome c oxidase subunit I (COI) gene, the genetic distance, the genetic tree of the leaffish and characterize the chemical physics of water of its habitat in the Kelekar River Muara Enim Regency and the Ogan River, Ogan Ilir Regency. The method used in species authentication was DNA isolation, amplification using PCR (Polymerase Chain Reaction) and sequencing of COI gene. The size of the COI mtDNA gene fragment was 704 bp (PM 1, PM 4, PP 2 and PP 4) and 723 bp (PM 2, PM 3, PP 1 and PP 3). A cryptic diversity of the species P. grooti is found based on the genetic distance value of 4.5-6%, both in the Kelakar and Ogan Rivers. The phylogenetic tree of the leaffish of this study formed 2 separate sub-clusters with a bootstrap value of 50%. The properties of water qualities in the two rivers included temperatures 28.3-31.8°C, pH 5.6-8.3, dissolved oxygen 4.82-10.89 mg L-1, alkalinity 10-28 mg L-1 CaCO3, water transparency 16-45 cm, ammonia 0.47-0.70 mg L-1, water current 0.17-0.30 m s-1 and TDS 7-44 mg L-1.